Morphological trends in arcade shape and size in Middle Pleistocene Homo. Issue 1 (23rd October 2018) - Stelzer, Stefanie; Neubauer, Simon; Hublin, Jean‐Jacques; Spoor, Fred; Gunz, Philipp
Abstract: Objectives: Middle Pleistocene fossil hominins, often summarized as Homo heidelbergensis sensu lato, are difficult to interpret due to a fragmentary fossil record and ambiguous combinations of primitive and derived characters. Here, we focus on one aspect of facial shape and analyze shape variation of the dental arcades of these fossils together with other Homo individuals. Materials and Methods: Three‐dimensional landmark data were collected on computed tomographic scans and surface scans of Middle Pleistocene fossil hominins ( n = 8), Homo erectus s.l. (n = 4), Homo antecessor ( n = 1), Homo neanderthalensis ( n = 13), recent ( n = 52) and fossil ( n = 19) Homo sapiens . To increase sample size, we used multiple multivariate regression to reconstruct complementary arches for isolated mandibles, and explored size and shape differences among maxillary arcades. Results: The shape of the dental arcade in H. erectus s.l. and H. antecessor differs markedly from both Neanderthals and H. sapiens . The latter two show subtle but consistent differences in arcade length and width. Shape variation among Middle Pleistocene fossil hominins does not exceed the amount of variation of other species, but includes individuals with more primitive and more derived morphology, all more similar to Neanderthals and H. sapiens than to H. erectus s.l. Discussion: Although our results cannot reject the hypothesis that the Middle Pleistocene fossil hominins belong to a single species, their shape variation comprises a more primitive morph that represents a likely candidate for the shape of the last common ancestor of Neanderthals and H. sapiens, and a more derived morph resembling Neanderthals. The arcade shape difference between Neanderthals and H. sapiens might be related to different ways to withstand mechanical stress.